FARMASI: PROFESI YANG TAK KALAH PENTING DARI DOKTER DALAM DUNIA KESEHATAN - Hafidhah, Nadira (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
In the healthcare system, the role of pharmacists is often underestimated compared to that of doctors. However, pharmacy plays a crucial role in ensuring patient safety through the provision and management of quality medications. This essay discusses how the pharmacy profession not only supports but also serves as an essential element in modern healthcare practice. Through an examination of the roles, regulations, and working relationships between doctors and pharmacists, the importance of collaboration among healthcare professionals is emphasized in delivering optimal patient care. With a foundation in legal and professional ethics, it is demonstrated that the success of patient therapy relies heavily on good interdisciplinary cooperation, including effective communication between doctors and pharmaceutical personnel.